MANAGEMENT OF HYPOTHYROIDISM IN GASTRIC OUTLET OBSTRUCTION USING LEVOTHYROXINE SOLUTION VIA ILEOSTOMY ROUTE - Yao , Hearty; Lopez , Lizette Kristine (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 64-year-old Filipino female with colon adenocarcinoma previously underwent hemicolectomy and ileostomy creation. She was maintained on oral levothyroxine 75μg tablet once daily for post-surgical hypothyroidism. She was placed on prolonged nothing per orem due to gastric outlet obstruction which hindered the delivery of oral levothyroxine resulting in hypothyroidism. Her thyroid function test showed elevated TSH at 23.2 uIU/ml and low normal free T4 at 0.7 ng/dl. Levothyroxine solution was prepared by dissolving 2 tablets of 150 μg levothyroxine in 50ml of plain saline solution administered via ileostomyroute using a French 24 foley catheter and dwelling for 2 hours before removal. We delivered levothyroxine solution via the ileostomy route at a dose range of 6.3 to 15 μg per kilogram per day to achieve euthyroid state with a normal free T4 level. A cost-effective and safe alternative route of levothyroxine administration for conditions prohibiting the enteral route of administration can be used.